Preparation method of P-Cat-MnO2 nanoflower battery positive electrode material and application of P-Cat-MnO2 nanoflower battery positive electrode material in aqueous zinc ion battery
By introducing phosphorus and carbon into manganese-based materials, the positive electrode material of P-C@MnO2 nanoflower battery was prepared, which solved the phase change, dissolution and irreversible ability of manganese-based materials in aqueous zinc ion batteries, achieving higher battery performance and lower production costs.
Patent Information
- Application Number
- CN202510119818.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-25
AI Technical Summary
The phase change, dissolution and irreversible ability of manganese-based materials in aqueous zinc ion batteries limits its performance and hinders the further development of the battery.
By introducing phosphorus and carbon during the synthesis process, the positive electrode material of P-C@MnO2 nanoflower battery was prepared, which increased the active site of the material, promoted the diffusion of ions and charge transfer, improved the conductivity and reduced the internal resistance.
It improves the specific capacity and circulation performance of aqueous zinc ion batteries, reduces production costs, enhances safety and environmental friendliness, and improves energy density and power density.
Smart Images

Figure CN119650672A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and specifically relates to a method for preparing a PC@MnO2 nanoflower battery positive electrode material and an application thereof in an aqueous zinc ion battery. Background Art
[0002] With the increasing concern about environmental issues and the high demand for sustainable energy, the development of new materials for high-performance energy storage and conversion is urgent. In addition, the global demand for renewable energy and environmentally friendly technologies is growing, and energy storage technology, especially efficient and environmentally friendly battery technology, has become a hot topic in research. In the past few decades, lithium-ion batteries have been widely selected as backup batteries in the energy field, from electric vehicles to household appliances. However, the limited lithium resources, rising prices and high risk factors have hindered the further development of lithium-ion batteries. In the context of resource limitations and environmental pressures faced by traditional battery technologies such as lithium-ion batteries, aqueous zinc-ion batteries stand out with their unique advantages.
[0003] Aqueous zinc-ion batteries, unlike traditional lithium-ion batteries, use neutral or weakly acidic zinc salt aqueous solutions as electrolytes (pH: 3.6-6.0), have low requirements for packaging conditions, low production costs, are safe and environmentally friendly, and have good development prospects in the field of large-scale energy storage. They are regarded by researchers as a more promising battery research direction. The electrochemical performance of zinc-ion batteries is highly dependent on their cathode materials. In recent years, the development of cathode materials has mainly focused on manganese-based materials, vanadium-based materials, Prussian blue and its analogs. Among them, manganese-based materials are considered to be the most promising cathode materials due to their different crystal structures and three-dimensional spatial frameworks. However, the unnecessary phase change, inevitable dissolution and undesirable reversibility of manganese-based materials have hindered their further development. This technology introduces phosphorus and carbon to increase its active sites, effectively promote ion diffusion and charge transfer, improve the conductivity of MnO2, reduce its internal resistance, and maintain the structural flexibility and stability of the material, thereby improving the overall performance of aqueous zinc-ion batteries. Summary of the invention
[0004] To solve the above problems, the present invention provides a method for preparing a PC@MnO2 nanoflower battery positive electrode material and its application in an aqueous zinc ion battery.
[0005] The technical solution adopted by the present invention is:
[0006] A PC@MnO2 nanoflower battery positive electrode material, the preparation method of which comprises the following steps:
[0007] 1) Glucose and P2O5 were quickly mixed in a 50 mL reactor for 5 min, then transferred to a stainless steel autoclave, and then heated to obtain a black expanded precursor;
[0008] 2) calcining the black expanded precursor in a tube furnace, then washing the obtained product to remove impurities, filtering and drying to obtain PC powder;
[0009] 3) Mix potassium permanganate and PC powder evenly, stir for 1 hour, dissolve in deionized water by ultrasonic for 10 minutes, perform hydrothermal reaction on the fully mixed solution, cool to room temperature, centrifuge and wash, and vacuum dry to obtain PC@MnO2 electrode material.
[0010] Furthermore, in the above-mentioned method for preparing the PC@MnO2 nanoflower battery positive electrode material, in step 1), the heating condition is heating at 200°C for 6 hours.
[0011] Further, in the above-mentioned method for preparing a positive electrode material of a PC@MnO2 nanoflower battery, in step 2), the calcination condition is to first heat to 450°C for 3h, then heat to 800°C for 3h in an argon environment, and the heating gradient is 5°C min -1 .
[0012] Furthermore, in the above-mentioned method for preparing a PC@MnO2 nanoflower battery positive electrode material, in step 3), the mass ratio is potassium permanganate:PC=0.63:0.05~0.15.
[0013] Furthermore, in the above-mentioned method for preparing the PC@MnO2 nanoflower battery positive electrode material, in step 3), the hydrothermal reaction conditions are 180° C. for 6 hours.
[0014] Application of a PC@MnO2 nanoflower battery positive electrode material as described in any of the above items in an aqueous zinc ion battery.
[0015] Furthermore, the above application method comprises the following steps:
[0016] 1) Preparation of positive electrode: After the PC@MnO2 electrode material is evenly mixed with the binder and the conductive material, a small amount of NMP is added as a solvent, and after being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with the PC@MnO2 electrode material;
[0017] 2) Preparation of negative electrode: Grind the zinc sheet with sandpaper to remove the oxide layer on the surface, and cut the polished zinc sheet into small discs with a diameter of 12 mm;
[0018] 3) Using the positive electrode sheet coated with PC@MnO2 electrode material prepared in step 1) as the positive electrode, the zinc sheet prepared in step 2) as the negative electrode, and 1M ZnSO4+0.1M MnSO4 as the electrolyte, an aqueous zinc ion battery is obtained.
[0019] Furthermore, in the above application method, in step 1), the binder is PVDF.
[0020] Furthermore, in the above application method, in step 1), the conductive material is Super-p.
[0021] Furthermore, in the above application method, in step 2), the thickness of the zinc sheet is 0.1 mm-0.2 mm, and the purity is 99%-99.99%.
[0022] The present invention has the following beneficial effects:
[0023] 1. The present invention introduces phosphorus and carbon during the synthesis process, thereby increasing the active sites, effectively promoting ion diffusion and charge transfer, improving the conductivity of MnO2, reducing its internal resistance, and maintaining the structural flexibility and stability of the material.
[0024] 2. The introduction of phosphorus and carbon improves the specific capacity and cycle performance of the material during the charge and discharge process.
[0025] 3. The electrode material of the present invention has the characteristics of low cost, environmental friendliness and high safety.
[0026] 4. The electrode material of the present invention has the advantages of higher energy density and power density.
[0027] 5. The synthesis process and assembly process of the present invention are simple, easy to operate and control, and suitable for continuous large-scale production.
[0028] 6. The method of the present invention is also applicable to other metal oxide positive electrode materials and has good versatility. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the SEM image of MnO2 and PC@MnO2 prepared in Example 1.
[0030] Figure 2 This is the GCD spectrum of MnO2 and PC@MnO2 prepared in Example 1.
[0031] Figure 3 It is the XRD pattern of MnO2 and PC@MnO2 prepared in Example 1.
[0032] Figure 4 This is the specific capacity diagram of MnO2 and PC@MnO2 prepared in Example 1. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0034] Example 1
[0035] (I) Preparation of PC@MnO2 electrode materials
[0036] First, 1 g of glucose and 5 g of P2O5 were weighed and mixed quickly in a 50 mL reactor for 5 min, then transferred to a stainless steel autoclave and heated to 200 °C for 6 h to obtain a black expansion precursor. Second, the black expansion precursor was placed in a tube furnace and heated to 450 °C for 3 h under an argon atmosphere, and then heated to 800 °C for 3 h, with a heating gradient of 5 °C min -1 Then, the obtained product was rinsed three times in deionized water and CS2 to remove impurities, filtered and dried in vacuum at 80°C to obtain PC powder. Finally, 0.63g potassium permanganate and 0.1g PC powder were weighed and dissolved in 40mL deionized water, stirred for 1h, ultrasonicated for 10min, and then hydrothermal reaction was carried out at 180°C for 6h. When the reactor was completely cooled to room temperature, the product was taken out, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, and vacuum dried for 24h to obtain PC@MnO2 electrode material.
[0037] (II) Preparation of MnO2 electrode materials
[0038] Weigh 0.63g potassium permanganate directly and dissolve it in 40mL deionized water, stir for 1h, ultrasonicate for 10min, and then perform hydrothermal reaction at 180℃ for 6h. When the reactor is completely cooled to room temperature, take out the product, wash it three times by centrifugation with deionized water and anhydrous ethanol respectively, and vacuum dry it for 24h to obtain MnO2 electrode material. The preparation method of MnO2 is similar to that of PC@MnO2, and the weighing ratio does not change. The difference is that no PC powder is added.
[0039] (III) Detection
[0040] Figure 1 is the SEM spectrum of MnO2 and PC@MnO2 prepared in this example. Figure 1 It can be seen that the prepared material is in the shape of uniform nanoflowers. Figure 2 is the GCD spectrum of MnO2 and PC@MnO2. Figure 2 It can be seen that the performance of the electrode material is significantly improved after doping. Figure 3 is the XRD spectrum of MnO2 and PC@MnO2. Figure 3 It can be seen that the XRD spectrum of the sample shows its characteristic peaks, indicating its successful composite. Figure 4 is the specific capacity diagram of MnO2 and PC@MnO2. Figure 4 It can be seen that the specific capacity of PC@MnO2 is much greater than that of pure MnO2.
[0041] Example 2 Preparation of PC@MnO2 electrode material
[0042] First, 1 g of glucose and 5 g of P2O5 were weighed and mixed quickly in a 50 mL reactor for 5 min, then transferred to a stainless steel autoclave and heated to 200 °C for 6 h to obtain a black expansion precursor. Second, the black expansion precursor was placed in a tube furnace and heated to 450 °C for 3 h under an argon atmosphere, and then heated to 800 °C for 3 h, with a heating gradient of 5 °C min -1 Then, the obtained product was rinsed three times in deionized water and CS2 to remove impurities, filtered and dried in vacuum at 80°C to obtain PC powder. Finally, 0.63g potassium permanganate and 0.05g PC powder were weighed and dissolved in 40mL deionized water, stirred for 1h, ultrasonicated for 10min, and then hydrothermal reaction was carried out at 180°C for 6h. When the reactor was completely cooled to room temperature, the product was taken out, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, and vacuum dried for 24h to obtain PC@MnO2 electrode material.
[0043] Example 3 Preparation of PC@MnO2 electrode material
[0044] First, 1 g of glucose and 5 g of P2O5 were weighed and mixed quickly in a 50 mL reactor for 5 min, then transferred to a stainless steel autoclave and heated to 200 °C for 6 h to obtain a black expansion precursor. Second, the black expansion precursor was placed in a tube furnace and heated to 450 °C for 3 h under an argon atmosphere, and then heated to 800 °C for 3 h, with a heating gradient of 5 °C min -1 Then, the obtained product was rinsed three times in deionized water and CS2 to remove impurities, filtered and dried in vacuum at 80°C to obtain PC powder. Finally, 0.63g potassium permanganate and 0.15g PC powder were weighed and dissolved in 40mL deionized water, stirred for 1h, ultrasonicated for 10min, and then hydrothermal reaction was carried out at 180°C for 6h. When the reactor was completely cooled to room temperature, the product was taken out, washed three times by centrifugation with deionized water and anhydrous ethanol respectively, and vacuum dried for 24h to obtain PC@MnO2 electrode material.
[0045] Example 4 Preparation of negative electrode material
[0046] A zinc sheet with a thickness of 0.1 mm and a purity of 99.99% is repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet is cut into small discs with a diameter of 12 mm for later use.
[0047] Example 5 Preparation of negative electrode material
[0048] A zinc sheet with a thickness of 0.2 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into small discs with a diameter of 12 mm for later use.
[0049] Example 6 Preparation of aqueous zinc ion battery
[0050] 1) Preparation of positive electrode: After the PC@MnO2 electrode material and MnO2 electrode material prepared in Example 1 are uniformly mixed with PVDF and Super-p respectively, a small amount of NMP is added as a solvent, and after uniform mixing, they are directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain positive electrode sheets coated with PC@MnO2 electrode material and MnO2 electrode material respectively;
[0051] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode material prepared in Example 4 was used as the negative electrode, and 1M ZnSO4+0.1M MnSO4 was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.
[0052] Example 7 Preparation of Aqueous Zinc Ion Battery
[0053] 1) Preparation of positive electrode: After the PC@MnO2 electrode material prepared in Example 2 and the MnO2 electrode material prepared in Example 1 are mixed evenly with PVDF and Super-p respectively, a small amount of NMP is added as a solvent, and after mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain positive electrode sheets coated with the PC@MnO2 electrode material and the MnO2 electrode material respectively;
[0054] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode material prepared in Example 4 was used as the negative electrode, and 1M ZnSO4+0.1M MnSO4 was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.
[0055] Example 8 Preparation of Aqueous Zinc Ion Battery
[0056] 1) Preparation of positive electrode: After the PC@MnO2 electrode material prepared in Example 3 and the MnO2 electrode material prepared in Example 1 are mixed evenly with PVDF and Super-p respectively, a small amount of NMP is added as a solvent, and after mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain positive electrode sheets coated with the PC@MnO2 electrode material and the MnO2 electrode material respectively;
[0057] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode material prepared in Example 4 was used as the negative electrode, and 1M ZnSO4+0.1M MnSO4 was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.
[0058] Example 9 Preparation of Aqueous Zinc Ion Battery
[0059] 1) Preparation of positive electrode: After the PC@MnO2 electrode material and MnO2 electrode material prepared in Example 1 are uniformly mixed with PVDF and Super-p respectively, a small amount of NMP is added as a solvent, and after uniform mixing, they are directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain positive electrode sheets coated with PC@MnO2 electrode material and MnO2 electrode material respectively;
[0060] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode material prepared in Example 5 was used as the negative electrode, and 1M ZnSO4+0.1M MnSO4 was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.
[0061] Example 10 Preparation of aqueous zinc ion battery
[0062] 1) Preparation of positive electrode: After the PC@MnO2 electrode material prepared in Example 2 and the MnO2 electrode material prepared in Example 1 are mixed evenly with PVDF and Super-p respectively, a small amount of NMP is added as a solvent, and after mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain positive electrode sheets coated with the PC@MnO2 electrode material and the MnO2 electrode material respectively;
[0063] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode material prepared in Example 5 was used as the negative electrode, and 1M ZnSO4+0.1M MnSO4 was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.
[0064] Example 11 Preparation of aqueous zinc ion battery
[0065] 1) Preparation of positive electrode: After the PC@MnO2 electrode material prepared in Example 3 and the MnO2 electrode material prepared in Example 1 are mixed evenly with PVDF and Super-p respectively, a small amount of NMP is added as a solvent, and after mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain positive electrode sheets coated with the PC@MnO2 electrode material and the MnO2 electrode material respectively;
[0066] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode material prepared in Example 5 was used as the negative electrode, and 1M ZnSO4+0.1M MnSO4 was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.
[0067] According to the six aqueous zinc ion batteries assembled in Examples 6 to 11 above, we found that Example 6 has the best electrochemical performance, and the specific capacity is improved at each current density (such as Figure 4 As shown). Since the positive electrode material in Example 1 is used in Example 6, 0.1 g of PC powder is added therein, indicating that the ratio is most suitable at this time, providing more active sites, so it is easier to store more zinc ions, and at the same time, it promotes the insertion and extraction of zinc ions, thereby improving its electrochemical performance.
Claims
1. A PC@MnO2 nanoflower battery positive electrode material, characterized in that: The preparation method thereof comprises the following steps: 1) Glucose and P2O5 were quickly mixed in a 50 mL reactor for 5 min, then transferred to a stainless steel autoclave, and then heated to obtain a black expanded precursor; 2) calcining the black expanded precursor in a tube furnace, then washing the obtained product to remove impurities, filtering and drying to obtain PC powder; 3) Mix potassium permanganate and PC powder evenly, stir for 1 hour, dissolve in deionized water by ultrasonic for 10 minutes, perform hydrothermal reaction on the fully mixed solution, cool to room temperature, centrifuge and wash, and vacuum dry to obtain PC@MnO2 electrode material.
2. A PC@MnO2 nanoflower battery positive electrode material according to claim 1, characterized in that: In step 1), the heating condition is heating at 200° C. for 6 h.
3. A PC@MnO2 nanoflower battery positive electrode material according to claim 1, characterized in that: In step 2), the calcination conditions are to heat to 450°C for 3 h and then to 800°C for 3 h in an argon environment, with a heating gradient of 5°C min -1 .
4. A PC@MnO2 nanoflower battery positive electrode material according to claim 1, characterized in that: In step 3), by mass ratio, potassium permanganate:PC=0.63:0.05-0.
15.
5. The PC@MnO2 nanoflower battery positive electrode material according to claim 1, characterized in that: In step 3), the hydrothermal reaction condition is 180° C. for 6 h.
6. Application of a PC@MnO2 nanoflower battery positive electrode material as described in any one of claims 1 to 5 in an aqueous zinc ion battery.
7. The use according to claim 6, characterized in that: The method comprises the following steps: 1) Preparation of positive electrode: After the PC@MnO2 electrode material is evenly mixed with the binder and the conductive material, a small amount of NMP is added as a solvent, and after being evenly mixed, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with the PC@MnO2 electrode material; 2) Preparation of negative electrode: Grind the zinc sheet with sandpaper to remove the oxide layer on the surface, and cut the polished zinc sheet into small discs with a diameter of 12 mm; 3) Using the positive electrode sheet coated with PC@MnO2 electrode material prepared in step 1) as the positive electrode, the zinc sheet prepared in step 2) as the negative electrode, and 1M ZnSO4+0.1M MnSO4 as the electrolyte, an aqueous zinc ion battery is obtained.
8. The use according to claim 7, characterized in that: In step 1), the binder is PVDF.
9. The use according to claim 7, characterized in that: In step 1), the conductive material is Super-p.
10. The use according to claim 7, characterized in that: In step 2), the zinc sheet has a thickness of 0.1 mm to 0.2 mm and a purity of 99% to 99.99%.
Citation Information
Patent Citations
Zinc ion battery and preparation method of MnO2 / C positive electrode material of zinc ion battery
CN109686925A
Nanocomposite oxide and preparation method thereof, and electrode
CN110391405A
Ternary composite electrode material, preparation method thereof and zinc ion battery
CN113707868A
Synthesis method of phosphorus-doped manganese dioxide and application of phosphorus-doped manganese dioxide in zinc ion battery
CN115579467A
Ternary-doped manganese dioxide and carbon nanotube composite material as well as preparation method and application thereof
CN117133887A